2014
DOI: 10.2147/nrr.s46156
|View full text |Cite
|
Sign up to set email alerts
|

“Can nurse work environment influence readmission risk?” – a systematic review

Abstract: Background: Readmissions have been targeted as events that can improve quality of care while reducing health care expenditures. While increasing evidence has linked nurse work environment to various patient outcomes, no systematic review has assessed evidence examining nurse work environment in relation to readmission. Methods: This review was guided by the Institute of Medicine's Standards for Systematic Reviews. Comprehensive searches were conducted in PubMed, CINAHL, and PsycINFO, and were complemented by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…We found that better unit work environments were associated with superior quality of care, both the overall quality of care and care improvement. This finding is consistent with results in previous research Ma et al, 2014Ma et al, , 2015aMcHugh and Ma, 2013). In a hospital-level multi-country study, the researchers found that hospitals with poor hospital work environments had more nurses reporting poor quality of care, and this association was common across countries .…”
Section: Discussionsupporting
confidence: 94%
“…We found that better unit work environments were associated with superior quality of care, both the overall quality of care and care improvement. This finding is consistent with results in previous research Ma et al, 2014Ma et al, , 2015aMcHugh and Ma, 2013). In a hospital-level multi-country study, the researchers found that hospitals with poor hospital work environments had more nurses reporting poor quality of care, and this association was common across countries .…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, findings from other researchers who examined other nursing factors at the unit level indicate the need to investigate the relationship between unit‐level work environments and HAPUs (Choi, Bergquist‐Beringer, & Staggs, ; Park, Boyle, Bergquist‐Beringer, Staggs, & Dunton, ). Therefore, our findings are consistent with previous studies that reported the impact of hospital‐level work environments on patient outcomes (Aiken, Clarke, Sloane, Lake, & Cheney, ; Ma, Shang, & Stone, ), and it also expands the understanding of unit work conditions in relation to patient outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…12 A recent study of Medicare patients with HF, AMI, and PN found that patients have significantly lower risk for 30-day readmissions when cared for in hospitals with better nurse work environments, nurse staffing, and/or more nurses with a bachelor's degree. 13 Hospitals with better nurse staffing were 25% less likely to be penalized under the HRRP.…”
Section: Introductionmentioning
confidence: 99%
“…15 Other hospital nursing factors shown to be predictive of patient outcomes, such as work environment, were rarely considered. 12,15 …”
Section: Introductionmentioning
confidence: 99%